The Willingness to pay for Quality Aspects of Durables: Theory and Application to the Car Market - Ismir Mulalic; Jan Rouwendal (Tinbergen Institute, 2011)
Conventional hedonic analysis measures willingness to pay for attributes on the basis of marginal fixed costs. We argue that in many cases variable costs are also affected by these attributes and that this should be taken into account. We develop a simple model to show that the marginal willingness to pay for a quality attribute has to be equal to the full marginal cost, which includes marginal fixed as well as variable costs. The model is applied to Danish data on car ownership and use. We use a nonparametric estimation procedure to estimate hedonic price functions for fixed and variable costs. We recover each consumer's marginal willingness to pay, the marginal fixed costs, and the marginal variable costs for car attributes using first-order conditions for utility maximization. We show that the marginal fixed and variable costs have the same (positive) sign and that both contribute substantially to the marginal willingness to pay. Estimation results suggest that marginal variable costs are on average about 20% of the full marginal costs. Finally, we estimate the distribution of the marginal rate of substitution between quality attributes and variable costs, which can be interpreted as a structural parameter, and we investigate how this marginal rate of substitution varies with household characteristics.
Keywords: C14; D46; L62; L68; 330; durable goods; willingness to pay; hedonic analysis; nonparametrics; car market; Kraftfahrzeug; Willingness to pay; Dauerhafte Konsumgüter; Hedonischer Preisindex; Nichtparametrisches Verfahren; Dänemark